2014
DOI: 10.1002/app.41755
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal design study on factors affecting the diameter of perfluorinated sulfonic acid nanofibers during electrospinning

Abstract: In this study, Nafion® NR 40 beads with polyethylene oxide (PEO) are fabricated into a nanofiber membrane using electrospinning. In particular, Nafion® beads in non‐toxic mixed solvent (EtOH and H2O) were blended with the carrier polymer PEO, which is the minor component in the solution responsible for the solution spinnability. The highest content of Nafion® in the nanofiber is 98.04%. To investigate the factors influencing the nanofiber diameter during electrospinning, an orthogonal design method was adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…A steeped slope in variation of diameter with concentration demonstrates that this response is more sensitive to concentration than standard deviation. As expected and mentioned in literature , solutions with a high polymer content would hinder the fiber‐extension process (in the bending instability region of the jet) due to the greater resistance of the solution in stretching by the surface charges on the jet. This will lead to relatively thicker nanofibers with enhanced non‐uniformity.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…A steeped slope in variation of diameter with concentration demonstrates that this response is more sensitive to concentration than standard deviation. As expected and mentioned in literature , solutions with a high polymer content would hinder the fiber‐extension process (in the bending instability region of the jet) due to the greater resistance of the solution in stretching by the surface charges on the jet. This will lead to relatively thicker nanofibers with enhanced non‐uniformity.…”
Section: Resultssupporting
confidence: 70%
“…Reducing the diameter of nanofibers from 142 nm to 94 nm enhanced the conductivity from 0.095 S/cm to 0.126 S/cm at 60°C and 100% RH, respectively . The studies of electrospinning parameters on the morphology of nanofibers as a proton conducting component in the membrane structure have mainly focused on Nafion , and limited works are available on the morphological control of SPEEKK , PBI‐PBz , and SPEEK nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…The schematic of fabrication of GO/Nafion nanofiber membranes is shown in Figure . Nafion solution was prepared according to the procedure described in our previous report . The GO dispersion and Nafion solution were mixed to prepare 0.1% and 0.2% GO/Nafion solutions separately.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, the parameters of electrospinning experiment were studied using an orthogonal design and analysis method. Therein, we observed that Nafion lacks the necessary chain entanglements and does not form fibers unless a suitable carrier polymer is added to the electrospinning solution.…”
Section: Introductionmentioning
confidence: 99%
“…The average fiber diameter ranges from 300 to 730 nm. Changes in the diameter will affect the pore structure of the nanofiber membranes (Song et al 2015).…”
Section: Study Of the Fiber Morphologymentioning
confidence: 99%